Analisis Hukum Waris dalam Kitab Fathul Muin pada Mata Pelajaran Kitab di Pondok Pesantren Raudlatul Muhibbin Al-Mustainiyyah Surakarta: Analysis of Inheritance Law in the Book of Fathul Muin in Book Subjects at the Raudlatul Muhibbin Al-Mustainiyyah Islamic Boarding School in Surakarta - David Maulana Afriandi Saputra; Yudhistira Dwi Maulana; Muhammad Al Maliki; Muhamad Rayhan Ramadhani; Fahmi Izzulhaq; Ramdhan Diba Permana (Litera Academica Publishing, 2026)
This research discusses the analysis of inheritance law in the Book of Fathul Mu'in which is taught in book subjects at the Raudlatul Muhibbin Al-Mustainiyyah Islamic Boarding School in Surakarta. The background to this research stems from the importance of understanding Islamic inheritance law as part of muamalah fiqh which has direct implications in the social life of Muslims, as well as the role of Islamic boarding schools as traditional educational institutions in preserving and teaching classical Islamic law. The aim of this research is to analyze the concept, application and relevance of inheritance law contained in Fathul Mu'in to the practice of book learning in the Islamic boarding school. This research uses a descriptive qualitative approach with a library research method supported by observations and interviews with caregivers and students. Data were analyzed through the stages of reduction, presentation and drawing conclusions. The research results show that Fathul Mu'in provides a systematic explanation of the parts of heirs, the causes of inheritance, as well as the principles of justice in the distribution of inherited assets according to Islamic law. In learning practices at Islamic boarding schools, this book is the main reference that helps students understand inheritance theory as well as its application in the social context of society.